Nomophobia and its Relationship with Depression, Anxiety and Stress among Undergraduate Medical Students in a District of West Bengal: A Cross-sectional Study - Tousif Ahamed; Ritu Ghosh; Malay Kumar Das; Dilip Kumar Das (Journal of Clinical and Diagnostic Research)
Introduction: Nomophobia is the fear or anxiety that individuals experience when they are without their smartphones or unable to use them. The implications of nomophobia among undergraduate medical students could be significant, as medical education is demanding and stressful. The extent of nomophobia may affect mental health status. The potential relationship between nomophobia and mental health, particularly depression, anxiety, and stress, is a subject of growing interest. Aim: This study aimed to estimate the magnitude of nomophobia, the prevalence and degree of depression, anxiety, and stress, as well as to assess the relationship between nomophobia and mental health status, and to identify the correlates of nomophobia among undergraduate medical students. Materials and Methods: A descriptive cross-sectional study was conducted at Murshidabad Medical College, West Bengal, India, between September to November 2023, among 222 undergraduate medical students from three consecutive batches (2020-21, 2021-22, 2022-23), selected through stratified random sampling. A self-reported questionnaire comprising the validated Nomophobia Questionnaire (NMP-Q) and the Depression, Anxiety, and Stress Scale (DASS) was used to collect data. Both bivariate and multivariable logistic regression analyses were applied to identify the predictor variables. Correlation analyses were conducted using Spearman’s coefficient. A p-value of 0.05 or below was considered statistically significant. Results: The mean age of the participants was 21.47±1.86 years, with a median age of 21.50 years. Among the participants, 151 (68.0%) were male, 145 (65.3%) were Hindu, and 196 (88.3%) belonged to nuclear families. The distribution of nomophobia among participants was as follows: 29 (13.1%) had mild, 160 (72.1%) had moderate, and 33 (14.8%) had severe nomophobia. Depression, anxiety, and stress were found to be present in 121 (54.5%), 154 (69.4%), and 83 (37.4%) of the participants, respectively. Significant predictors of severe nomophobia included students aged under 21 years (aOR: 6.088; 95% CI: 2.053–18.055), those belonging to joint families (aOR: 6.836; 95% CI: 2.392–19.537), and those who used smartphones for more than five hours daily (aOR: 5.314; 95% CI: 1.919–14.721). Nomophobia was significantly correlated with depression (Spearman’s rho: 0.200, p-value=0.003) but not with anxiety and stress. Conclusion: Nomophobia is universally prevalent among medical students, with varying severity. The findings suggest the need for targeted health education interventions for the holistic well-being of medical students.